A biodegradable thermosensitive hydrogel vaccine for cancer immunotherapy. (June 2020) - Yang, Fan; Shi, Kun; Jia, Yanpeng; Hao, Ying; Peng, Jinrong; Yuan, Liping; Chen, Yu; Pan, Meng; Qian, Zhiyong
Highlights: This vaccine activates and mature DCs both in vitro and in vivo. This vaccine releases immunomodulators and antigens in a sustained manner. This vaccine prolongs overall survival time of tumor-bearing mice. This vaccine maintains a higher level of tumor necrosis factor in the serum. This hydrogel may serve as an easily manufactured vaccine delivery platform. Abstract: Although existing nanomaterial-based strategies for the recruitment and activation of dendritic cells (DCs) for cancer immunotherapy have achieved promising results, many issues related to safety and effectiveness remain unresolved. Simpler and safer designs are thus urgently required to eradicate tumors. In this study, we engineered an injectable and biodegradable thermosensitive hydrogel vaccine encapsulating GM-CSF, CpG-ODN (a TLR 9 agonist) and tumor cell lysates (TLs). The results confirm that this formulation of the vaccine can significantly activate and mature DCs both in vitro and in vivo due to its ability to release immunomodulators and antigens in a sustained manner. Surprisingly, on day 14, compared to controls, the hydrogel vaccine maintained a higher level of tumor necrosis factor (TNF) in the serum, which suggested it promoted a direct killing effect on tumors. When B16F10 or C26 tumors were immunized with TLs, the hydrogel vaccine observably delayed tumor growth and prolonged overall survival time in both prophylactic and therapeutic trials. In addition, an optimal formulation of this system was established to achieve the most effective inhibition of tumors. Our findings suggest that this hydrogel system may serve as an easily manufactured vaccine delivery platform for cancer immunotherapy.